Classification and Processing Optimization of Barley Milk Production Using NIR Spectroscopy, Particle Size, and Total Dissolved Solids Analysis - Jasenka Gajdoš Kljusurić; Maja Benković; Ingrid Bauman (Journal of Chemistry)
Barley is a grain whose consumption has a significant nutritional benefit for human health as a very good source of dietary fibre, minerals, vitamins, and phenolic and phytic acids. Nowadays, it is more and more often used in the production of plant milk, which is used to replace cow milk in the diet by an increasing number of consumers. The aim of the study was to classify barley milk and determine the optimal processing conditions in barley milk production based on NIR spectra, particle size, and total dissolved solids analysis. Standard recipe for barley milk was used without added additives. Barley grain was ground and mixed in a blender for 15, 30, 45, and 60 seconds. The samples were filtered and particle size of the grains was determined by laser diffraction particle sizing. The plant milk was also analysed using near infrared spectroscopy (NIRS), in the range from 904 to 1699 nm. Furthermore, conductivity of each sample was determined and microphotographs were taken in order to identify the structure of fat globules and particles in the barley milk. NIR spectra, particle size distribution, and conductivity results all point to 45 seconds as the optimal blending time, since further blending results in the saturation of the samples.